Efeito da topologia molecular no empacotamento cristalino de Pirazolo[1,5-a]pirimidinas - Tier, Aniele Zolin (2013)
This study shows the influence of the molecular topology of the crystal of a series of 14 pyrazolo[1,5-a]pyrimidines. The topological data were obtained from X-ray diffraction data and energy stabilization were determined by thermal analysis and chemical computations. Topological analysis carried out was Molecular Coordination Number (NCM) using the Voronoi-Dirichlet polyhedra and Hirshfeld surface. The NCM found for the majority of compounds was 14. Furthermore, it was determined contact area and the solid angle between molecules of the first coordination sphere of the cluster. Several correlations between data were performed, where it is possible highlight the correlation between the area of contact of the cluster molecules and the interaction energy and the solid angle and interaction energy were established. These correlations showed that there is a proportionality between the data, showing that the greater the contact area, the greater the interaction energy for a series of pyrazolo[1,5-a]pyrimidine studied in this thesis. As the contact area, solid angle also presents proportionality with the calculated interaction energy. Among the atom-atom contacts present on the surface of the test compounds was observed that contacts C∙∙∙H and C∙∙∙C are key to stabilize the crystals. This result corroborates the hypothesis that the contact surface between the molecules would be the driving force for the crystalline arrangement.